Administrative Procedure and the Inter-American Human Rights System. Zulima Sánchez Sánchez - Méndez Vásquez, Diego Enrique (Revista de Derecho, 2024)
The study of the procedure as a true legal institution is still under construction and Professor Sánchez's book is added to this purpose. This work consolidates, systematises and abstracts the bases of the jurisprudence of the Inter-American Human Rights System in relation to administrative procedure as a tool for controlling the actions of the public administration.